Trajetória de minha formação acadêmica: jornada rumo ao conhecimento - Campelo, Sara Bernado (Brasil, 2024)
Throughout my academic journey, I have experienced significant experiences that transcend the limits of the classroom and extend into the professional and personal sphere. This final work seeks to recap and reflect on the lessons learned from my college education, in addition to addressing the contributions of internships to my professional and personal growth. I also intend to explore the intersection between my professional and personal life, highlighting how these aspects intertwine and influence each other.